Neutronic properties of high-temperature gas-cooled reactors with thorium fuel; Annals of Nuclear Energy; Vol. 113 - Shamanin I. V. Igor Vladimirovich; Grachev V. M. Viktor Mikhaylovich; Chertkov Yu. B. Yuri Borisovich; Bedenko S. V. Sergey Vladimirovich; Mendoza O. Quiroz Orlando Jose; Knyshev V. V. Vladimir Vladimirovich (2018, 2018)
Title screen